Strengthening the competitiveness of MSMEs at Batujajar transit apartment through financial literacy training - Harlina, Putri Widyanti; Lembong, Elazmanawati; Wulandari, Endah (Universitas Muhammadiyah Magelang, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a crucial role in driving local economies, yet many operators still lack adequate understanding of effective financial management. Low financial literacy often results in difficulties in determining the Cost of Goods Sold (COGS), maintaining simple financial records, and formulating long-term business strategies. This community service program aimed to strengthen the capacity of MSME actors, specifically residents of the Batujajar Transit Apartment, through participatory training. The methodology involved interactive lectures, group discussions, and hands-on practice, integrated with the student Community Service Program (KKN) of Universitas Padjadjaran. The program successfully demonstrated an increase in participant understanding, reflected in their ability to calculate basic COGS, create financial recording formats, and produce relevant Business Model Canvas (BMC) drafts. Evidence of success is visible in the BMC examples developed by the participants. It is expected that this activity will enhance the product competitiveness of the MSMEs through more professional business governance and financial management.